Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1161/jaha.118.010365
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Ablation of Ventricular Tachycardia in Patients With Arrhythmogenic Right Ventricular Cardiomyopathy/Dysplasia: A Sequential Approach

Abstract: Background It has been suggested that endocardial and epicardial ablation of ventricular tachycardia ( VT ) improves outcome in arrhythmogenic right ventricular cardiomyopathy/dysplasia. We investigated our sequential approach for VT ablation in patients with arrhythmogenic right ventricular cardiomyopathy/dysplasia in a single center. Methods and Results We included 47 patients (44±16 years) with definite (81%) or b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…Prior studies of patients undergoing VT ablation have shown a large variability in reported outcomes. [3][4][5][6][7][8][9][10][11][12] In general the most promising results have been demonstrated in from highvolume single-centers using an epicardial ablation strategy, which has been increasingly utilized throughout the last decade. 4,5,7,10 These studies have reported VT-free survivals ranging from 91% after a median follow up of 11 months to 71% after 56 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies of patients undergoing VT ablation have shown a large variability in reported outcomes. [3][4][5][6][7][8][9][10][11][12] In general the most promising results have been demonstrated in from highvolume single-centers using an epicardial ablation strategy, which has been increasingly utilized throughout the last decade. 4,5,7,10 These studies have reported VT-free survivals ranging from 91% after a median follow up of 11 months to 71% after 56 months.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies have reported varying results on the procedural efficacy. [3][4][5][6][7][8][9][10][11][12] These studies have predominantly been conducted at large referral centers specialized in VT ablation and therefore the results may not reflect the general effect of VT ablation due to the selection and high volume in these centers. Therefore, the purpose of this study was to evaluate predictors and use of VT ablation and the post-procedural long-term outcome in a large multicenter cohort of patients with ARVC.…”
Section: Introductionmentioning
confidence: 99%
“…If ECG criteria anticipated left ventricular access, retrograde transaortic and/or antegrade transseptal puncture was performed after epicardial puncture to avoid access under heparinization. Electrophysiological study, mapping and ablation were performed as described by our group previously [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Pericardial access was performed as previously described [ 17 ]. Until February 2012 the largest part of epicardial ablation procedures were regularly performed fluoroscopically guided in AP view with a 14-gauge cannula (Angiocath, Becton Dickinson, Sandy, UT, USA) in an inferior and left medioclavicular oriented direction, between the left border of the subxiphoid and the rib cage, the so-called Larrey’s gap (Figs.…”
Section: Methodsmentioning
confidence: 99%
“…In concordance with the findings in this report, a recent publication showed no significant difference in clinical outcome between an endocardial and endocardial-epicardial approach in patients with ARVC, with a substantial proportion of patients receiving only endocardial ablation, not needing further epicardial ablation. 8…”
Section: Case Reportmentioning
confidence: 99%